IDENTIFYING COMMUNITY BASED TOURISM POTENTIAL IN SAPIT VILLAGE THROUGH SWOT ANALYSIS - Muhammad Adi Junaidi; Amrullah Amrullah; Evilia Rochmi (Kepariwisataan: Jurnal Ilmiah, 2025)
AbstractThis study aims to identify the potential for developing Sapit Village as a community-based tourism village through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. Sapit Village, located in Lombok Timur Regency, West Nusa Tenggara Province, offers diverse natural and cultural attractions such as mountain nous landscapes, traditional weaving, and authentic agricultural practices, yet these assets remain suboptimally managed within a sustainable tourism framework. Employing a qualitative case study approach, data were gathered via participatory observation, in-depth interviews with community leaders, tourism practitioners, and policymakers, and documentation review of village development plans and tourism regulations. Internal (strengths and weaknesses) and external (opportunities and threats) factors were mapped to formulate locally relevant development strategies. Findings indicate that Sapit Village’s primary strengths include its natural endowments, cultural heritage, active community engagement, and creative-economic potential (e.g., weaving and agritourism). Key challenges involve inadequate infrastructure, limited human-resource capacity, and non-professional institutional management. Opportunities arise from supportive tourism policies, experiential-tourism trends, digital-technology advances, and strategic partnership prospects. External threats encompass environmental degradation, cultural erosion, digital-access disparities, and natural-disaster risks. The study concludes that an integrative, participatory development approach balancing social, economic, cultural, and environmental dimensions, is essential. These insights provide strategic guidance for regional authorities, local communities, and stakeholders in designing inclusive, sustainable tourism-village development. Future research should further explore quantitative assessments of visitor preferences, longitudinal studies on community capacity building, and comparative analyses with other emerging tourism villages to enrich the strategic framework and ensure broader applicability.Keywords: Tourism Village; SWOT; Empowerment; Sustainable Tourism; Strategy